338 The Impact of an Aspergillus Oryzae Prebiotic on Mineral Bioavailability in Multiparous Beef Cows Supplemented with Vitaferm Concept-aid. (21st September 2022) - Podversich, Federico; Schulmeister, Tessa M; Tarnonsky, Federico; Alfaro, Gastón; da Silva, Gleise Medeiros; de Martinez, Juan Jesus Vargas; Maderal, Araceli; Gonella, Angela M; Ipharraguerre, Ignacio R; DiLorenzo, Nicolas
Abstract: This study aimed to evaluate the effect of supplementation with an Aspergillus oryzae prebiotic (AOP) fed from ~30 d pre-partum until 30 d post-partum, on mineral concentrations in blood, liver, colostrum, and milk of multiparous beef cows. Thirty pregnant Angus crossbred cows were offered ad libitum Bermuda grass hay (Cynodon dactylon) plus a Vitaferm Concept-Aid (Biozyme Inc., St Joseph, MO) supplement at a rate of 112 g, containing (AOP; n = 15) or not (CTL; n = 15) an AOP. The treatments were delivered individually with a dried distillers grains-based premix at 454 g/d using an automated feeder (C-lock Inc, Rapid City, SD). For a minimum of 60 days prior to the expected calving date, the cows did not receive any mineral supplementation. Approximately 30 days prior to calving, right before supplementation began, blood and liver samples were collected, and mineral concentrations were used as a baseline. At calving (d 0) colostrum and blood samples were collected. Blood sampling, liver biopsies and milk collections were performed within one week after calving (d 7), and 30 days post-partum (d 30). All samples were analyzed to determine mineral concentration of P, Ca, Mg, Co, Cu, Fe, Zn, Mo, Mn, and Se. Concentrations of most micro minerals ranged from marginally adequate to deficient, with small improvement over time. Cows fed AOP had 11 and 14% lesser P and Se concentrations in serum, respectively (P < 0.05). Conversely, cows fed AOP had greater concentrations of Mn concentration in milk by 34% (P ≤ 0.05), and greater Cu in milk by 74% on day 7 (P < 0.05). Feeding AOP did not affect (P > 0.10) the mineral concentrations in liver nor in colostrum. In conclusion, feeding AOP may affect mineral bioavailability in beef cows as evidenced by changes in milk mineral concentrations.